Figli su commissione: profili civilistici della maternità surrogata in Italia dopo la legge 40/2004 (TEST BioLaw Journal - Rivista di BioDiritto, 2014)
Surrogacy, widespread in some States of the U.S.A., Asia and continental Europe, is a reproductive practice prohibited in Italy, according to article 12, paragraph 6, of the Italian Law no. 40/2004 about the artificial reproduction. The present paper – after a brief recognition of the case?law, previous and following to the approval of the new law – tries to respond to the main legal issues deriving from the violation of the domestic prohibition realised into the national territory, particularly in relation to the effects of surrogacy contract and to the correct institution of the parental relationship with the new?born baby.
Keywords: artificial reproduction; natural motherhood; parental relationships; surrogacy contract; surrogate motherhood.